2022
DOI: 10.5455/msm.2022.34.118-120
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Yoga Practice on Level of Stress During COVID-19 Pandemic

Abstract: Background: The COVID-19 pandemic has become a major cause of stress and anxiety worldwide. It has generated stress among people from all sections of society, especially to workers who have been assigned to cater to healthcare service or those constrained to secure daily essential items. Yoga practice is actively sought to achieve reduced anxiety and stress so that improved sleep may positively impact immunity. Objective: The aim of this cross-sectional study was to determine whether those who practice Yoga d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…A cross-sectional study has shown the benefit of yoga amidst the COVID-19 lockdown [5]. When compared to those not practicing yoga, females attending yoga sessions during the pandemic demonstrated a significantly lowered severity of stress symptoms [5].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study has shown the benefit of yoga amidst the COVID-19 lockdown [5]. When compared to those not practicing yoga, females attending yoga sessions during the pandemic demonstrated a significantly lowered severity of stress symptoms [5].…”
Section: Introductionmentioning
confidence: 99%